Pelatihan Pembelajaran Apresiasi Sastra Berorientasi Afirmasi Literasi Diri Bagi Guru SD di Tasikmalaya - Seni Apriliya; Erwin Rahayu Saputra (Universitas Negeri Makassar, 2023)
The concept of self-literacy can be interpreted as self-literacy. This understanding of self-literacy needs to be cultivated at the right time, especially at the elementary school level. For this reason, this training activity aims to make teachers in Tasikmalaya understand self-literacy and can implement the P-IKADKA model as a learning model for literary appreciation in the classroom oriented to self-literacy affirmations. The achievement of these goals is carried out through training activities with lecture methods, discussions, and guided exercises. The results of the training show that teachers can understand self-literacy and can apply the P-IKADKA model design well. This activity is able to provide new insights and experiences to teachers in implementing the concept of self-literacy and is able to improve the ability of teachers to carry out story appreciation learning, especially those oriented to self-literacy affirmations. After the teachers gain insight and experience, it is hoped that they will be able to implement it in learning at school so that it has an impact on elementary school students who have awareness about themselves, understand themselves and respect themselves and others..Keywords: literacy, self-literacy, literary appreciation, P-IKADKA model